PENERAPAN MODEL PEMBELAJARAN JIGSAW II UNTUK MENINGKATKAN PARTISIPASI SISWA DAN HASIL BELAJAR DALAM PEMBELAJARAN KIMIA UNSUR KELAS XII IPA 5 SMA KOLESE DE BRITTO YOGYAKARTA - HERIBERTUS SURADI (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2023)
This research was conducted against a background of class XII IPA 5 students who grew up in the digital world era, the boring Elemental Chemistry material causes students to lack active participation in learning activities, tend to be busy alone, and do not understand the learning material. The focus of the study is to increase student participation and learning outcomes in a conducive learning atmosphere through the Jigsaw II learning model. This study aims to explain the increase in student participation and learning outcomes using the Jigsaw II model in Elementary Chemistry learning for class XII IPA 5 SMA Kolese De Britto Yogyakarta. The research method used is Classroom Action Research with 2 cycles. The research was carried out by forming study groups consisting of 4 students who had low, moderate, and capable abilities in terms of knowledge. Was given an assignment on Elemental Chemistry material, then presented it in a presentation, and observed that finally a post test was carried out. The results of the study using the Jigsaw II learning model increased student participation seen from the involvement of students in groups during presentations. The final result of the assessment of cycle I was 37% incomplete and the average post-test score obtained was 78.56. Because there are still 37% that have not been completed, cycle II is carried out. The final result of the assessment in cycle II was that 11% of students had not finished and the average post-test score obtained was 88.81. ABSTRAKPenelitian ini dilakukan dengan latar belakang siswa kelas XII IPA 5 yang bertumbuh dalam era dunia digital, materi Kimia Unsur yang membosankan menyebabkan siswa kurang partisipasi aktif dalam kegiatan pembelajaran, cenderung ramai sendiri, dan kurang memahami materi pembelajaran. Fokus kajian adalah meningkatkan partisipasi siswa dan hasil belajar dalam suasana belajar yang kondusif melalui model pembelajaran Jigsaw II. Penelitian ini bertujuan untuk menjelaskan peningkatan partisipasi siswa dan hasil belajar menggunakan model Jigsaw II dalam pembelajaran Kimia Unsur kelas XII IPA 5 SMA Kolese De Britto Yogyakarta. Metote penelitian yang digunakan yaitu Penelitian Tindakan Kelas dengan 2 siklus. Penelitian dilakukan dengan membuat kelompok belajar yang beranggotakan 4 siswa yang mempunyai kemampuan rendah, cukup, dan mampu dari segi pengetahuan. Diberikan tugas tentang materi Kimia Unsur, kemudian menyajikan dalam presentasi, dan diobservasi akhirnya dilakukan postes. Hasil penelitian menggunakan model pembelajaran Jigsaw II meningkatkan partisipasi siswa dilihat dari keterlibatan siswa dalam kelompok pada saat presentasi. Hasil akhir penilaian dari siklus I adalah 37 % belum tuntas dan rata-rata nilai postes yang diperoleh 78,56. Karena masih ada 37 % yang belum tuntas maka dilakukan siklus II. Hasil akhir penilaian pada siklus II adalah 11 % siswa belum tuntas dan rata-rata nilai postes yang diperoleh adalah 88,81.